Efficacy of Nasal Steroids in Treatment of Adenoidal Hypertrophy in Children - Khan, Azam (International Journal of Pathology, 2022)
Background: The Adenoids (Pharyngeal tonsils) undergo hypertrophy till 7 years of age, showing maximum enlargement at the age of 4 years, it atrophies/ vanishes by the time adulthood sets in. This study will assess the effect of intranasal steroids in the treatment of adenoidal hypertrophy in our population. Significant data has not been collected with regards to the efficacy of intranasal steroids in conservative management of Adenoid Hypertrophy in our population to prevent the burden of surgery in such patients. Objective: To assess the efficacy of intranasal steroids in the treatment of hypertrophy of adenoids in children preventing the need for adenoidectomy. Methodology: A Randomised Control Trial was conducted at the ENT department of Hayatabad Medical Complex over a period of 6 months on 444 patients. The patients were randomly assigned into two groups by consecutive non probability sampling: one which had received intranasal steroid (Mometasone Furoate 100umg per day for 8 weeks) and the other group was given only placebo (saline nasal spray). Results: In Group A mean age was 7 years (SD ± 5.21) whereas in Group B mean age was 7 years (SD ± 5.57). In Group A 122 (55%) children were male while 100 (45%) were female whereas in Group B 127 (57%) children were male and 95 (43%) were female. Group A (Intranasal steroid) was effective in 195 (88%) children and was not effective in 27 (12%) children. In Group B (Saline nasal spray) was effective in 164 (74%) children and was not effective in 58 (26%) children. Conclusion: Our study concludes that intranasal steroids are more effective than nasal saline spray in the treatment of hypertrophy of adenoids in children, preventing the need for adenoidectomy.